Application Analysis Process Competence Personality Lecturer In Class Student in Sociology of Education Studies Program Faculty of Teaching and Education University Tanjungpura Pontianak - Imran, Imran (Jurnal Pendidikan Sosiologi dan Humaniora, 2017)
This study aims to analyze the process of implementing the personal competence of lecturers in carrying out the lecturing process comprising aspects of steady and stable, mature, wise, noble and role models for student. This research uses, descriptive method ferifikatif the form of case studies with the number of respondents as many as 80 people. The results of this study indicate that the majority of 95% of lecturers, in courses of study Sociology Education FKIP University Tanjongpura already own and carry personal competence well in the lecture students, comprising, aspects 1) Steady and Stable, 2) Adults, 3) Arif, 4) authoritative, 5) and a good moral example for students.Keywords: Personality Competence Education Lecturer Sociology.